The Society of Equals in the Woman on the Edge of Time by Marge Piercy (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Encouraged by the ideas of second-wave feminism, Piercy writes Woman on the Edge of Time, in which she attempts to apply the theoretical findings of her predecessors and contemporary authors. Her work echoes the theories of Simone de Beauvoir and Shulamith Firestone, which she applies in order to create Mattapoisett, a utopia in which the entire society tries to achieve progress together. In this paper, we will analyze the way Piercy twists certain categories of today – class, gender and race – and renders them meaningless so as to create her utopia. In the first part, we will pay attention to Connie’s present, to her position as a Mexican-American woman from the lower class, that is, her position as a person on the margins of society. We will also analyze the representations of motherhood in her circumstances. In the second part, we will focus on the ways Piercy creates a more just society which is reflected in gender-neutral language and gender-neutral people, a society in which there is no hierarchy which fetters Connie in her present. We will also pay special attention to the concept of abolishing the biological family, which is presented as a significant basis of such a society. By abolishing the traditional categories of the present, Piercy demonstrates the possibility of not a better future, but a future of equality that invites the reader to re-examine set values and create new ones.
Keywords: utopia; gender; motherhood; biological family